Non-immune Hydrops Fetalis and Hepatic Dysfunction in a Preterm Infant With Congenital Syphilis - Jessica Duby; Jessica Duby; Ari Bitnun; Ari Bitnun; Vibhuti Shah; Vibhuti Shah; Patrick Shannon; Patrick Shannon; Shiri Shinar; Shiri Shinar; Hilary Whyte; Hilary Whyte (Frontiers Media S.A., 2019)
We report a case of a preterm infant with congenital syphilis who presented with non-immune hydrops fetalis. Hepatic dysfunction was present at birth and acutely worsened following antibiotic administration. Placental pathology demonstrated infiltration with numerous spirochetes. Although critically ill, the infant recovered with intravenous penicillin G and supportive care. This case demonstrates that congenital syphilis remains a contemporary disease demanding enhanced awareness from clinicians. Manifestations evident in utero or in the newborn can be severe and may result in fetal demise or neonatal death. Moreover, we hypothesize that the treatment resulted in a Jarisch-Herxheimer reaction as manifested by the hepatic deterioration. The incidence of congenital syphilis and its associated complications can be greatly reduced with strict adherence to universal prenatal testing and comprehensive follow-up.